PERAN SITUS JEJARING SOSIAL DALAM PERSEPSI RESELLER - Rozi, M Fatkhur (Fakultas Ekonomi, UIN Maliki Malang, 2014)
The rapid development and growth of social networking sites in Indonesia raises opportunities forsales activity mainly resellers. Sales activity via the social networking site is an outgrowth of an earlierconcept that e-marketing. The purpose of this study wanted to gain an understanding of the role of the resellersocial networking sites. Methods used in this study is the Focus Group Discussion with 12 people resellersmobile products and clothing as participants. The results of the study explained that social networking sitesis an Internet-based tool that serves as a medium of communication for the promotion, negotiation, andtransaction. Of exposure obtained explanations focus group discussions that social networking sites are ameans of informing bid, bid development, and role as a reseller. The role of social networking sites is as amedium for conveying information, interactions, and transactions.